Social inequality and climate change. Student awareness: teachers-to-be and engineers-to-be on the links between social inequality and climate change on the basis of empirical research - Ocetkiewicz, Iwona; Mróz, Anna; Tomaszewska, Barbara; Sowiżdżał, Anna (Bulletin of Geography. Socio-economic Series, 2024)
The paper presents the results of research into the opinions of university students on the causes and consequences of climate change in the context of social inequalities. The main problem of the research was formulated in the following way: How do students (future teachers and future engineers) view the links between climate change and social inequalities? The main aim was to see how students’ opinions differed from one another. The authors wanted to find out how different characteristics affect perceptions of the causal relationship between the climate crisis and social inequalities. The majority of students at both universities chose indirect answers, showing that they are not fully convinced of the strong links between the climate crisis and social inequalities. This shows a need for intensive, multi-faceted measures to help students to recognise the relationships between these two aspects.